1999
DOI: 10.1089/mdr.1999.5.265
|View full text |Cite
|
Sign up to set email alerts
|

Activity of 16 Antimicrobial Agents Against Drug-Resistant Strains ofMycobacterium tuberculosis

Abstract: The in vitro activity of 16 antimicrobial agents against 46 drug-resistant strains of Mycobacterium tuberculosis recently isolated from Italian patients was determined. As for first-line antituberculosis drugs, while isoniazid was ineffective against all the strains tested, resistance to streptomycin, rifampicin, pyrazinamide, and ethambutol was 80.4%, 71.7%, 39.1%, and 8.7%, respectively. Among second-line antituberculous drugs, resistance to ciprofloxacin, ofloxacin, and sparfloxacin and to amikacin and kana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 11 publications
(1 reference statement)
0
25
0
Order By: Relevance
“…Sequencing analysis showed that all the 10 MT isolates carried the same katG GGG3AGG G234R allele, suggesting that the same strain persisted over time. The DNA fingerprinting results on IS6110 confirmed that all sequential isolates belonged to a unique strain (data not shown) (7).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Sequencing analysis showed that all the 10 MT isolates carried the same katG GGG3AGG G234R allele, suggesting that the same strain persisted over time. The DNA fingerprinting results on IS6110 confirmed that all sequential isolates belonged to a unique strain (data not shown) (7).…”
Section: Resultsmentioning
confidence: 70%
“…The clinical isolates were genotyped by IS6110-based restriction fragment length polymorphism analysis to exclude the presence of different strains (7,9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutation conferring resistance to RMP is TCG531TTG (Ser3Leu) in the rpoB gene (4,15); the mutation conferring resistance to INH is AGC315ACC (Ser3Thr) in the katG gene (unpublished data). Comparative MICs of these and other drugs for isolate RM22 and for a susceptible M. tuberculosis strain, H37Rv (ATCC 27294), as determined by the twofold agar dilution technique on Middlebrook 7H11 agar (Difco Laboratories, Detroit, Mich.) (4)(5)(6)13), are shown in Table 1. INH, CM, CS, PAS, EMB, SM, KM (Sigma Chemical Co., St. Louis, Mo.…”
mentioning
confidence: 99%
“…8 Recently, the Italian National Institute of Health (ISS) showed that, among second-line antitubercular drugs, only about 10% of the 46 drug-resistant strains of M tuberculosis isolated from Italian patients were resistant to capreomycin. 9 To overcome CS's toxic effects on kidneys, site-specific delivery systems can be employed. In particular, it has been demonstrated that entrapment of CS in multilamellar vesicles (MLVs) reduced renal toxicity, enhanced peptide penetration into tissues, and increased CS activity in a beige mouse model of M avium complex infection.…”
Section: Introductionmentioning
confidence: 99%